Extração e purificação dos compostos fenólicos presentes nas folhas de Camellia sinensis - Sousa, Larissa dos Santos (2016)
The teas from Camellia sinensis plant are traditionally used medicinal form due to the fact they contain bioproducts with antioxidant power and are able to prevent and even cure some diseases like cancer. The products responsible for the benefits in human health are the catechins, polyphenols low molecular weight class. Membrane separation technology can be used for clarification, purification, or concentration for different products. Thus, this paper aims to extract and purify the phenolic compounds present in green, black and white tea, using water as a solvent for extraction and membranes for purification. The leaves of Camellia sinensis were subjected to infusion at the concentration of 100 g of leaves into 1 L of water, at first was analyzed the extraction of phenolic compounds at temperatures ranging from 30 to 80 ° C for different times (0 to 120 min), and the extract was filtered through filter cloth. Subsequently analyzed as pre-treatment with chitosan (20 to 100 ppm), centrifugation (20 min at 80000 rpm) and microfiltration (cellulose ester membranes with porosity of 0,22, 0,3 and 0,8 μm to 0,7 bar). The ultrafiltration process was performed at 6 bar and the feed was the permeate from the microfiltration membrane with a 0.8 μm pore size. The ultrafiltration membranes used was from NADIR polyethersulfone with molecular weight cutoff of 5, 10, 20 and 30 kDa, in a process with recycle. The ultrafiltration tests were also conducted with application of ultrasound and electromagnetic field. The flows obtained from the micro and ultrafiltration was used to calculate the fouling mechanism (applying mathematical model, to define the mechanism responsible for the decay of flow) and to calculate the resistance of the membranes. All these procedures were first performed with green tea and the process that best results were used for black tea and white tea. Samples obtained in each case were analyzed for the concentration of phenolics (Folin-Ciocalteu reagent), turbidity, color intensity, the concentration of solids, proteins and chromatographic analysis (HPLC). It was also analyzed the formation of tea cream front of the micro and ultrafiltration processes, and for this the samples were stored under refrigeration (5 °C) for 16 h. It was observed that compared to the results of pre-treatments that chitosan was obtained a better reduction of solids contained in the extract (56,22%), but microfiltration membrane with porosity of 0,8 μm was used as pre ultrafiltration-treatment as well as reducing the concentration of solids, showed low reduction of phenolic compounds and showed higher stabilized flow value (10,27 kgm-2h-1). Among the different conditions applied in the ultrafiltration, ultrasound has lower resistance, increase in flux (12,24%) stabilized, reduction of rejection of phenolic compounds (25,64%) and the permeate was stable even after 30 days storage under refrigeration. For green tea permeated analyzed EGCG, which was obtained in larger amount (39,55%) for the 20 kDa membrane in the conventional process. . For the process using ultrasound this value increased to 41,60%. Thus, it is concluded that micro and ultrafiltration processes can be applied and the permeate obtained in the ultrafiltration are more stable than the microfiltration and had purified phenolic compounds.